Caracterização da assinatura isotópica de Pb atual e da concentração de metais pesados em sedimentos de fundo da foz do rio Guamá e da Baía do Guajará (Belém - Pará) - NASCIMENTO, Suziane Magalhães do (Universidade Federal do Pará, 2022)
The city of Belem launches a significant amount of domestic pollutants in natura and industrial effluents in the Guama river and the Guajara bay. Previous studies suggest that the bottom sediments deposited in the edges of the river and the bay have its chemical composition influenced by these anthropogenic inputs. The aim of this work is to characterize the Pb isotopic signature, associated to the study of the distribution of the concentration of Pb and other heavy metals (Cu, Cr and Ni) in bottom sediments from the hydrographic system of Belem (Guama river and Guajara bay), in order to evaluate the regional natural variations and to evidence possible anthropogenic contributions from the industrial and urban activities of the city of Belem. Thirty three georeferenced samples of bottom sediments from the Guama river and from the Guajara bay were collected, using a Petersen grab, with capacity to sample the first 10 cm of muddy sediments. Fourteen samples came from the left edge of the Guama river, including the Cumbu and Great islands, until it flow into the bay and nine samples from the right edge, at the city riverside. Nine samples of bottom sediments were also collected from the Guajara bay, beside eight samples from the islands (Jaguar, Jutuba, Jararaca and Mirin) and one from the riverside of Belem for the determination of heavy metal contents and Pb isotopic composition. At the laboratory, samples were dried in an oven (50°C), disaggregated in a agate mortar and sieved down to 63μm, for the separation of the fine fraction (silt + clay). The mineralogical composition of the fine fraction was determined by X-rays diffraction. The total and partial heavy metals concentrations were determined, respectively, by ICP-MS at commercial laboratory (Acme Ltda), and by ICP-OES at the Toxicological Laboratory of the Instituto Evandro Chagas, Belem. The determination of the Pb isotopic compositions was carried out on samples previously leached using HNO3 at the Para-Iso Laboratory of the Instituto de Geociencas - UFPA, and using a mixture HNO3 + HCl at the Geochronological Laboratory of the Centro de Pesquisas Geocronologicas - USP. The Pb separation and purification were carried out by ionic exchange chromatography. The Pb isotopic compositions have been determined by TIMS on a monocollector mass spectrometer VG Isomass 54E with, at the laboratory of UFPA and on a multicollector mass spectrometer VG354 at the laboratory of the USP. The results indicate that the mineralogical composition of the fine fraction of the sediments includes smectite, illite and Kaolinite. Chemical analyses of heavy metals furnished the following total and partial contents for the samples from the Guama river right edge: PbTotal (11-23 mg.Kg-1); PbPartial (9-18 mg.Kg-1); 10 CrTotal (26-69 mg.kg-1); CrPartial (11-23 mg.kg-1); NiTotal (7-29 mg.Kg-1); NiPartial (6-26 mg.Kg-1); CuTotal (7-23 mg.Kg-1); CuPartial (6-17 mg.Kg-1). For the samples from the left edge of the river, the following total and partial concentrations were obtained: PbTotal (16-20 mg.Kg-1), Pbpartial (13–19 mg.Kg-1); CrTotal (34-56 mg.kg-1), Crpartial (16-26 mg.kg-1); NiTotal (12-21 mg.Kg-1), Nipartial (12-16 mg.Kg-1), Cutotal (9-14 mg.Kg-1) and Cupartial (7-12 mg.Kg-1). The sediments from both edges of the Guama river similarly display a slight decrease of heavy metal contents downstream, in the direction of the bay. However, the sediments at south of the left edge islands display an increase of contents in the same direction. Variation in the dynamic of aquatic system of the Guama river by combined effect of currents and tides would probably account for such an opposite behavior. For the sediments from the right edge, significant variations of the metals contents were locally identified and are considered to be due to the confluence of the Aura tributary, which provokes local disturbs in the hydrodynamic of Guama river as well as a redistribution of the metals along the right edge of the river at a local scale. Physical-chemical conditions of the Aura water are probably modified by the effects of the Belem waste deposit, located on the edge of the river, by increasing of the metals solubility that may account for lower heavy metal contents of the bottom sediments from the Aura river up to the confluence with the Guama river. Consequently, the Aura river will not provide any significant input of heavy metals in the Guama river. Correlation diagrams display a good correlation between heavy metals and the organic matter and excellent correlations with Al, Mg and the Fe (r = 0.95-0.99) for the samples of the right edge of the Guama river, indicating that the heavy metals are associated to the organic matter, adsorbed by the clay-minerals (smectite, illite and Kaolinite) and, probably, associated to iron oxy-hydroxides, though they have not identified. Samples of the left edge did not provide any correlation of Pb and Cr with organic matter (r = 0.24 and 0.40), however excellent correlations were identified with Al and Fe (r = 0.94-0.97). Cu and Ni are poorly correlated with organic matter (r = 0.59 and 0.72) while the correlations with Al, Mg and Fe are good (r = 0.74-0.89). Therefore, clayminerals and, possibly, iron oxy-hydroxides prevail for heavy metals contents. The sediments of both edges of the Guama river have, respectively, total concentrations of Pb (23 and 20 mg Kg-1) and Cu (23 and 14 mg Kg-1) lower than the 35 mg Kg-1 (Pb) e 36 mg Kg-1 (Cr) values of TEL (Threshold effect level), established by the NOAA-EPA as a guide of quality of sediments and that defines the level below of which adverse biological effects will rarely occur. Then, sediments of the Guama river, even so they are in contact with domestic pollutants, do not represent any 11 risk, at the moment, for the aquatic ecosystem, at least regarding to Pb and Cu. The total concentrations of Cr (69 and 53 mg Kg-1) and Ni (26 and 18 mg kg-1), for the sediments of the right and left edges, respectively, are higher than or equal to the respective TEL values of 37 and 18 mg kg-1 for these metals and may constitute a risk for aquatic organisms of the Guama river. However, such Cr and Ni concentrations come probably from natural sources without any significant anthropic influences. The homogeneous isotopic signature of the sediments of the Guama river, together with the low Pb concentrations indicate a geogenic origin for this metal and allow to establish a value for the regional "background" of Pb concentration around 18-23 mg Kg-1. They also allow considering an isotopic signature of 1.200-1.194 for the 206Pb/207Pb ratios of Pb from natural sources, reinforcing the values previously proposed by Moura et al. (2004). The lower contents of Pb found in some samples from the right edge of the Guama river (11-13 mg Kg-1), associated to slightly anthropogenic isotopic signature (1.186 < 206Pb/207Pb < 1.193) are interpreted as a result of the influence of the Aura tributary on the sediments of the Guama river. The significant increase of Pb contents in the stream sediments of the Guajara bay is an indicator of possible future biological risks in the hydrographic system of Belem. The well established negative correlation between Pb concentrations (28-46 mg Kg-1) and 206Pb/207Pb isotopic ratios (1.172 < 206Pb/207Pb < 1.188), discards the possibility that the increase of Pb contents in the Guajara bay to be of geogenic origin and that the difference in concentration with the Guama river to be resulted only of distinct hydrodynamic processes.